2020
DOI: 10.14474/ptrs.2020.9.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of neuromuscular control exercise on neck pain, range of motion, and proprioception in persons with neck pain

Abstract: Objective: This study aimed to investigate the immediate effects of intervention using neuromuscular control, self-stretching (SS), and neck stabilization exercises (NSEs) on neck pain, range of motion (ROM), and proprioception of position sense in adults with neck discomfort. Design: Three-group pretest-posttest design. Methods: Forty-four adults who complained of neck pain participated in the experiment. They were randomly assigned to the following groups: neuromuscular control exercise (NMCE) group (n=15), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
(29 reference statements)
2
6
0
1
Order By: Relevance
“…The PSO algorithm takes inspiration from this model. It assumes that the solution of each optimal problem corresponds to a bird in the search area and is represented by a “particle” [ 14 ]. Each “particle” will have a value determined by an adaptive function.…”
Section: Influence Algorithm Of Exercise Biomechanics In Martial Arts...mentioning
confidence: 99%
“…The PSO algorithm takes inspiration from this model. It assumes that the solution of each optimal problem corresponds to a bird in the search area and is represented by a “particle” [ 14 ]. Each “particle” will have a value determined by an adaptive function.…”
Section: Influence Algorithm Of Exercise Biomechanics In Martial Arts...mentioning
confidence: 99%
“…Lee and Shin [ 23 ] evaluated 44 patients suffering neck pain divided into three groups: a neuromuscular control exercise group (upper limb pattern rolling exercises), a self-stretch group, and a neck stabilization exercise with the pressure biofeedback device group. In comparison, the neuromuscular control exercise group showed a significant reduction in pain in comparison to the results of the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Ginn et al [25] demonstrated that exercises to restore neuromuscular control were as effective as corticosteroid injections in treating shoulder pain in the short term. In addition to the shoulder, NME has a significant therapeutic effect on many other musculoskeletal pain conditions, such as low back pain [39,40], neck pain [41], chronic musculoskeletal pain in the elderly [42], chronic pain after primary total knee arthroplasty [43], and knee and hip osteoarthritis [44,45]. NME includes active exercises of strength, coordination, balance, and proprioception.…”
Section: Evaluation Of the Effect Of Neuromuscular Exercise On Painmentioning
confidence: 99%